2014
DOI: 10.3906/sag-1303-87
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile ocular blood flow changes after panretinal photocoagulation treatment in patients with proliferative diabetic retinopathy

Abstract: Although for ultrabasic and basic magmas a plethora of tectonomagmatic diagrams have been used, with the exception of one bivariate diagram for refined tectonic setting of orogenic andesites, none is available for highly abundant intermediate magma.We present 3 sets of discrimination diagrams obtained from the correct statistical methodology of log e -ratio transformation and linear discriminant analysis. All major element log e -ratio variables in 3664 samples, only immobile major and trace element log e -rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 357 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…Exclusion criteria included (1) previous laser treatments; (2) prior vitreoretinal surgery (vitrectomy, intravitreal triamcinolone injection) in the study eye; (3) history of any thromboembolic event (including myocardial infarction or cerebral vascular accident); (4) major surgery within the prior 6 months; (5) glaucoma under treatment or elevated IOP (above 21 mm Hg Goldmann applanation tonometry); (6) known coagulation abnormalities or current use of anticoagulant medication other than aspirin; (7) evidence of external ocular infection (conjunctivitis, keratitis, or significant blepharitis); (8) refractive error ±3.0 SD; (9) history of antihypertensive medication use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria included (1) previous laser treatments; (2) prior vitreoretinal surgery (vitrectomy, intravitreal triamcinolone injection) in the study eye; (3) history of any thromboembolic event (including myocardial infarction or cerebral vascular accident); (4) major surgery within the prior 6 months; (5) glaucoma under treatment or elevated IOP (above 21 mm Hg Goldmann applanation tonometry); (6) known coagulation abnormalities or current use of anticoagulant medication other than aspirin; (7) evidence of external ocular infection (conjunctivitis, keratitis, or significant blepharitis); (8) refractive error ±3.0 SD; (9) history of antihypertensive medication use.…”
Section: Methodsmentioning
confidence: 99%
“…The gold standard treatment for proliferative diabetic retinopathy treatment is panretinal laser photocoagulation. The impact of panretinal photocoagulation (PRP) on intraocular pressure (IOP) levels has been studied before (1)(2)(3) but the effect of PRP on ocular pulse amplitude (OPA) has rarely been the focus of reported investigations.…”
Section: Introductionmentioning
confidence: 99%
“…This observation raises speculations that PRP exacerbates the postoperative inflammatory response, interferes with venous blood reflux in the choroid, and induces changes in local hemodynamics and opening of the capillary bed. These factors contribute to choroidal and ciliary body edema and exudation, 59 as well as forward movement of the iris root, narrowing of the anterior chamber angle, obstruction of aqueous humor outflow pathways, and subsequent elevation of intraocular pressure. 60 , 61 Meanwhile, the study 45 also found that patients undergoing membrane segmentation during surgery appear to have a lower risk of increased intraocular pressure.…”
Section: Risk Factorsmentioning
confidence: 99%